Beyond Sight & Sound: A Brief Introduction to Sensory Communication: A Review of Professor May Lwin’s Lecture at MHM 2025 - Meng, Yutong (The Journal of Medicine, Humanity and Media, 2025)
With the rapid development of digital media, contemporary communication practices are undergoing a profound transformation of “disembodiment.” Vision and hearing have gradually become the dominant channels of information transmission, while embodied senses such as smell and touch have been systematically marginalized. This article is based on the inaugural lecture of the MHM2025 special series delivered by Professor May Lwin, titled "Beyond Sight & Sound: A Brief Introduction to Sensory Communication." In the lecture, Professor Lwin emphasized that marginalized senses such as olfaction and haptics play irreplaceable roles in brand recognition, health communication, and the construction of user trust, while also reflecting cultural embeddedness and cross-cultural variation. Particularly in Asian contexts, she highlighted the urgency of developing culturally localized olfactory tools and haptic frameworks to improve the effectiveness and equity of health communication. The lecture provides both theoretical insight and practical direction for advancing sensory communication studies globally and calls for a paradigm shift toward re-embodiment in communication research.